Cyclic voltammetry in the absence of excess supporting electrolyte: The effect of analyte charge - Belding, SR; Compton, R (2012)
The cyclic voltammetry of the simple electrochemically reversible reduction, A ZA+ne⇌B ZB, is modelled using numerical simulations. The effect of adding different concentrations of supporting electrolyte is studied as a function of the scan rate, the diffusion coefficients of species A and B and the diffusion coefficients of the ions in the supporting electrolyte. These studies cover the following Z A/Z Bredox couples: 2/1, -1/-2, 8/7, and -7/-8. The supporting information contains a table listing the minimum concentration of supporting electrolyte required to achieve fully supported voltammetry pertaining to a range of scan rates (10 -1≤Fνre2 DART≤10 5); a wide range of charges of the electroactive species (-7≤ ZA≤8) and includes both one and two electron transfer. This allows experimental conditions to be defined so that any particular Nernstian electrochemical system may be studied under diffusion-only conditions without the need for additional experiments and/or simulations. © 2012 Elsevier B.V. All rights reserved.